Analisis Struktur Modal Berbasis Informasi Manajemen: Studi Berbasis Perspektif Manajerial - Dandi Aprila; Dewi Cahyani Pangestuti (LP2M Politeknik Jambi, 2025)
This study explores how capital structure decisions at PT ABC, a property developer managing both an apartment project and an office building were shaped, implemented, and subsequently tested when market conditions shifted unexpectedly. Adopting a qualitative approach, the research draws on in-depth interviews with key managerial personnel as well as an examination of financing agreements, project cash-flow reports, and internal planning documents. The findings reveal that PT ABC’s initial financing decisions were anchored in optimistic expectations regarding presales and rental income, with minimal consideration of downside scenarios or market volatility. As apartment sales slowed and office occupancy weakened, the company’s cash flow deteriorated, leading to breaches of critical loan covenants, including the DSCR requirement. These breaches triggered delays in loan disbursements and further constrained project progress. In response, management initiated several adaptive measures such as renegotiating loan terms, offering substantial price discounts to accelerate cash inflows, and implementing cost-cutting efforts. These actions reflect a strong reliance on internal financing consistent with the Pecking Order Theory, although they proved insufficient to fully counter the pressures created by the weakening market. Overall, the study underscores the importance of more conservative capital structure planning, rigorous cash-flow stress testing, and early-warning systems for covenant risks in navigating the cyclical and highly sensitive dynamics of the property sector.